Ice, mountains, and people: applying a multi-proxy approach to reveal changes in Alberta’s alpine ecosystems through ice patch research - Tirlea, Diana; Kristensen, Todd; Osicki, Aaron; Jensen, Britta; Williams, Krista; Caners, Richard; Lumley, Lisa; Woywitka, Robin (My University, 2023)
Glacial archaeology has grown and progressed rapidly in recent decades with technological innovations and shifting socio-political issues. However, research on ice patches in the Canadian Rocky Mountains is in its infancy. While Holocene glacial ice retreat, advance, and morphology are well studied in Canada, ice patches in general tend to be understudied because of their limited geomorphological impact on landscapes. This oversight is concerning as their isolated nature, lower elevation, and small mass make ice patches even more susceptible to climate change than glaciers. The importance of documenting these features is heightened by a persisting but tenuous biological importance to a range of modern species. The lack of flow in ice patches also makes them excellent archives of palaeoenvironmental and organic-based cultural materials, as layers of ice and preserved contents are not as distorted as they may be by flow in glaciers.
Keywords: ice patches; Canadian Rocky Mountains